Reading and making notes - Godfrey, Jeanne (Palgrave Macmillan, 2015)
A little book that takes students clearly through the important differences between the 'why' and 'how' of reading at university. It shows how to use reading lists, journals and books effectively, and how to put together coherent, useful notes. With this book, students will make the best possible use of their time spent reading.